A blue light carbon dot based on boron and nitrogen co-doping and its preparation method and application
By preparing blue light carbon dots based on boron-nitrogen co-doping, combining poly(9-vinylcarbazole) and ortho-dichlorobenzene, an efficient light-emitting diode was constructed, and the problem of low efficiency of existing blue light carbon dot light-emitting diodes was solved, and the problem of low efficiency of existing blue light carbon dot light-emitting diodes was achieved. Efficient and environmentally friendly luminous effect.
Patent Information
- Application Number
- CN202411288699.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing blue-light carbon dot light-emitting diodes have low efficiency and cannot break through the 5% external quantum efficiency limit. In addition, traditional carbon quantum dot materials have problems of toxicity and high cost.
Blu-ray carbon dots (BN-CDs) based on boron nitrogen co-doped by solvothermal reaction were prepared by using benzeneboric acid and m-phenylenediamine as precursors, and used them as guest materials, combining poly(9-vinylcarbazole) and O-dichlorobenzene, prepare a mixed solution of the luminescent layer to build an efficient light emitting diode.
The photoluminescence fluorescent quantum yield of blue light carbon dots has reached 86.41%, and the external quantum efficiency of the light emitting diode is improved through phosphorescence emission, breaking through the 5% limit of traditional materials, and the material is safe and environmentally friendly.
Smart Images

Figure CN118792048B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical materials, and in particular relates to a blue light carbon dot based on boron and nitrogen co-doping, and a preparation method and application thereof. Background Art
[0002] Organic light emitting diodes (OLEDs) are a new generation of flat panel display technology with advantages such as high luminous efficiency and brightness, fast response speed and low driving voltage. However, organic light emitters usually have the disadvantages of complex synthesis methods, complex device manufacturing and high cost, which greatly limit their widespread commercial application. In this context, heavy metal-based quantum dots (QDs) and perovskites, which are characterized by solution processability, bright and tunable photoluminescence emission dependent on size / composition, have been developed as promising candidates for LEDs. With the rapid development of this field in recent years, light-emitting diodes (QLEDs) prepared based on quantum dots have attracted widespread attention from researchers around the world. QLEDs have unique advantages such as high color saturation, adjustable emission color, high brightness and simple solution processing capabilities. They have been widely used in the fields of display and lighting. Compared with OLEDs, they have better color saturation and simpler preparation conditions, which have unique advantages. However, heavy metals (such as Cd) in traditional quantum dots and perovskites are not as abundant as those in traditional quantum dots and perovskites. 2+ and Pb 2+ ) has serious toxicity, and the prepared LEDs have unavoidable problems such as high toxicity, low stability and high cost. Taking advantage of the high stability, low cost, environmental friendliness, non-toxicity and pollution-free of carbon materials, efficient carbon-based luminescent materials not only enhance the prospects of the next generation of carbon photonic and optoelectronic technology frontiers, but also provide a new possibility for the lighting and display fields. Carbon dots (Carbon Dots, CDs) have attracted great attention in optoelectronic devices, especially electroluminescent LEDs. Therefore, carbon-based light-emitting diodes (Carbon Dots Light-Emitting Diodes, CDLEDs) prepared based on carbon dots have attracted much attention.
[0003] In practical applications, the three luminescent materials of blue, green and red corresponding to the three primary colors of LED are the basis for realizing high color rendering index lighting applications and wide color gamut display applications. At present, the development trend of green and red light in the market is good (thanks to phosphorescent materials), which can meet the needs of commercialization, but the development of blue light materials is relatively lagging, which is mainly due to the contradiction between its inherent optical requirements and electrical requirements. At the same time, the research and development of blue light materials that meet the requirements of high efficiency and high color purity is still quite challenging. In addition, blue light LED is the key factor in realizing display and lighting in all saturated spectral emissions, and it is also the cornerstone of producing saturated white light in LED technology applications. How to develop cost-effective, environmentally friendly, low-toxic, and efficient luminescent materials and construct blue light emitting diodes is a huge challenge.
[0004] The performance of CDLED devices needs to be evaluated from two aspects: optical performance and electrical performance. The main performance indicators include external quantum efficiency (EQE), current efficiency (CE, cd A -1 ), Power Efficiency (PE, lm W -1 )、Starting voltage( V on , V), maximum luminous brightness ( L max , cd m -2 ), color coordinates (Color Index Coordinates, CIE), efficiency roll-off, etc.
[0005] External quantum efficiency: The ratio of the number of photons emitted by a device to the number of carriers injected. The calculation formula is:
[0006]
[0007] Where g is the carrier recombination rate. Ideally, carrier injection and transport are balanced, and the carrier recombination rate is 100%. is the exciton utilization rate; is the photoluminescence efficiency, i.e., the fluorescence quantum yield of the luminescent material; It is the light output efficiency. Without considering the light extraction coupling effect and the special structure that enhances the light output, it is generally believed that the light output efficiency is 20-30%.
[0008] In summary, the development of high-efficiency and stable CDLED devices is of great significance, and the luminescent layer material plays a dominant role in CDLED devices, so the development and research of excellent CDs is very important. According to the above calculation formula, high-luminous efficiency carbon dot materials are the basic conditions for the preparation of high-efficiency CDLEDs. Most of the technologies currently constructed for CDLEDs fail to exceed 5% EQE.
[0009] For example, patent CN 115697001A discloses a method for preparing a light-emitting diode based on carbon quantum dots. The prior art uses 2,5-dihydroxyterephthalic acid as the first precursor and phenylenediamine as the second precursor to prepare blue carbon quantum dot fluorescent powder B-CQDs. B-CQDs-m and poly(9-vinylcarbazole) (PVK) are weighed respectively, and o-dichlorobenzene is used as the solvent to prepare a mixed solution of the device light-emitting layer. The CLED device with a doping concentration of 20% has the highest efficiency of 4.83%, and the efficiency of the CLED device with a doping concentration of 5% is 4.27%. The defect of the prior art is that the LED based on pure fluorescent CQDs cannot overcome the spin-forbidden nature of the singlet-triplet transition. The light emission of the prepared CLED device only utilizes the singlet excitons of the fluorescence, which ultimately leads to the efficiency of the CLED device failing to break through the 5% EQE limit of the fluorescence emission based on CQDs. Summary of the invention
[0010] The purpose of the present invention is to provide a blue light carbon dot based on boron and nitrogen co-doping and its preparation method and application, so as to solve the problems existing in the above-mentioned prior art. The present invention uses phenylboric acid as a first precursor and m-phenylenediamine as a second precursor, and reacts at different molar ratios to prepare a series of blue light carbon dots BN-CDs based on boron and nitrogen co-doping, and then uses BN-CDs with the highest photoluminescence fluorescence quantum yield as a guest material, poly (9-vinyl carbazole) as a main material, and o-dichlorobenzene as a solvent to prepare a light-emitting layer mixed solution, which is used as a light-emitting layer raw material to prepare a light-emitting diode based on blue light carbon dots co-doped with boron and nitrogen.
[0011] One of the technical solutions provided by the present invention:
[0012] A method for preparing blue-light-emitting carbon dots based on boron-nitrogen co-doping, using phenylboric acid as a first precursor and m-phenylenediamine as a second precursor through a solvothermal reaction, to prepare BN-CDs (blue-light-emitting carbon dots based on boron-nitrogen co-doping).
[0013] Preferably, the preparation method of blue light carbon dots based on boron-nitrogen co-doping comprises the following steps: mixing phenylboric acid, m-phenylenediamine and an organic solvent, performing a solvent thermal reaction after ultrasound, cooling the reactants to room temperature, separating and purifying them by column chromatography, and then performing rotary evaporation and vacuum drying to obtain blue light carbon dots based on boron-nitrogen co-doping.
[0014] Preferably, the usage ratio of the phenylboric acid, m-phenylenediamine and the organic solvent is (0.12-1.83) g: (0.11-2.16) g: (10-20) mL.
[0015] When the dosage of phenylboronic acid is too much, it may lead to the presence of more electron-withdrawing groups in the epitaxial functional groups of the synthesized carbon dots, forming electron-hole recombination centers, increasing the probability of non-radiative transitions, and ultimately leading to lower luminescence efficiency of the carbon dots; when the dosage of phenylboronic acid is too little, it may lead to less boron doping, weakening the complementary resonance effect of the electron density distribution on the HOMO and LUMO orbits, thereby affecting the conductivity and luminescence properties of CDs, and ultimately affecting the luminescence efficiency of the device.
[0016] Preferably, the temperature of the ultrasound is 30-60°C and the time is 30-60 min.
[0017] Preferably, the solvent thermal temperature is 180-220° C. and the time is 360-720 min.
[0018] Solvothermal reaction is when the reactants are dispersed in the solution and become more active, the reaction occurs, and the product is slowly generated. The lining material of the reactor is polytetrafluoroethylene, and its softening temperature is 250℃. When in use, it is strictly forbidden to use it at overtemperature and overpressure, and the maximum temperature is ≤220℃. When the temperature is too high, it may easily lead to severe creep, which may cause leakage and cause accidents; when the temperature is too low, the reactants may only partially dissolve, and the reactants may not react with each other, further resulting in poor uniformity and dispersion of the reaction liquid, easy agglomeration, incomplete reaction, affecting the formation of strong covalent bonds and hydrogen bond networks during the reaction process, causing the size, morphology, physical phase and other properties of the final product to be affected, thereby affecting the EQE of the device.
[0019] The second technical solution provided by the present invention is:
[0020] A blue light carbon dot based on boron and nitrogen co-doping is prepared by the above preparation method.
[0021] The third technical solution provided by the present invention is:
[0022] A preparation method for a light-emitting diode comprises the following steps: using the above-mentioned blue-light carbon dots based on boron and nitrogen co-doping as a guest material, poly (9-vinyl carbazole) as a main material, and o-dichlorobenzene as a solvent to prepare a light-emitting layer mixed solution, cleaning the surface of an ITO substrate, drying, and then treating with ozone, and placing in a nitrogen environment for standby use; spin-coating a PEDOT:PSS solution on the treated surface of the ITO substrate to form a film, and annealing at 100-150°C for 15-30min to form a PEDOT:PSS film; spin-coating the light-emitting layer mixed solution on the PEDOT:PSS film, and then annealing at 100-150°C for 15-30min; in a vacuum environment filled with nitrogen, using a thermal deposition method to prepare an electron transport layer, an electron injection layer and an aluminum electrode, and preparing a light-emitting diode based on blue-light carbon dots based on boron and nitrogen co-doping.
[0023] Preferably, the amount ratio of the blue light carbon dots based on boron and nitrogen co-doping, poly(9-vinylcarbazole) and o-dichlorobenzene is (0.3-2) mg: (9.7-8) mg: (1-10) mL.
[0024] Preferably, the thickness of the electron transport layer is 40-80 nm, the thickness of the electron injection layer is 0.5-5 nm, and the thickness of the aluminum electrode is 80-150 nm.
[0025] More preferably, the method for preparing a light-emitting diode based on boron-nitrogen co-doped blue carbon dots of the present invention comprises the following steps:
[0026] 1) Mix phenylboric acid, m-phenylenediamine and ethanol, wherein the amount ratio of phenylboric acid, m-phenylenediamine and ethanol is (0.12-1.83) g: (0.11-2.16) g: (10-20) mL, and ultrasonicate at a temperature of 30-60° C. for 30-60 min; after treatment, perform solvent thermal reaction at a temperature of 180-220° C. for 360-720 min, cool to room temperature, separate and purify, perform rotary evaporation and vacuum drying to obtain BN-CDs;
[0027] 2) Using BN-CDs as the guest material, poly(9-vinyl carbazole) as the host material, and o-dichlorobenzene as the solvent, a mixed solution of the light-emitting layer is prepared, wherein the amount ratio of BN-CDs, poly(9-vinyl carbazole) and o-dichlorobenzene is (0.3-2) mg: (9.7-8) mg: (1-10) mL;
[0028] 3) Clean the surface of the ITO substrate, then ultrasonically clean it with acetone, anhydrous ethanol and deionized water respectively, dry it, then treat it with ozone, and place it in a nitrogen environment for standby use;
[0029] 4) Spin coating the PEDOT:PSS solution onto the treated ITO substrate surface to form a film. During the spin coating process, the rotation speed of the PEDOT:PSS solution is 4000-6000r / 30-60s, and then annealing is performed at 100-150°C for 15-30min to form a PEDOT:PSS film;
[0030] 5) Spin coating the luminescent layer mixed solution prepared in step 2) onto the PEDOT:PSS film, wherein the rotation speed of the luminescent layer mixed solution during the spin coating process is 2000-5000r / 30-60s, and then annealing at 100-150°C for 15-30min;
[0031] 6) In a vacuum environment filled with nitrogen, the vacuum degree is 10 -5 Pa, an electron transport layer, an electron injection layer and an aluminum electrode are prepared by thermal deposition method, wherein the electron transport layer has a thickness of 40-80nm, the electron injection layer has a thickness of 0.5-5nm, and the aluminum electrode has a thickness of 80-150nm, and a light-emitting diode based on blue light carbon dots co-doped with boron and nitrogen is constructed.
[0032] Compared with the prior art, the present invention has the following advantages and technical effects:
[0033] The invention uses phenylboric acid as a first precursor and m-phenylenediamine as a second precursor to prepare pure blue carbon dot powder BN-CDs with a blue light carbon dot fluorescence quantum yield of up to 86.41% and an emission wavelength of 430 nm, and then uses BN-CDs as a guest material, poly (9-vinylcarbazole) as a main material, and o-dichlorobenzene as a solvent to prepare a luminescent layer mixed solution, which is used as a luminescent layer raw material to prepare a high-efficiency light-emitting diode with good structural stability based on boron-nitrogen co-doped carbon dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0035] Figure 1 Schematic diagram of the preparation process of BN-CDs in Example 1;
[0036] Figure 2 a) is a transmission electron microscope (TEM) image of the BN-CDs prepared in Example 1, b) is a high-resolution transmission electron microscope (HRTEM) image of the BN-CDs prepared in Example 1, and c) is a particle size distribution diagram of the BN-CDs prepared in Example 1;
[0037] Figure 3 is the X-ray diffraction (XRD) pattern of the BN-CDs powder prepared in Example 1;
[0038] Figure 4 This is the Raman spectrum of BN-CDs prepared in Example 1;
[0039] Figure 5 is the Fourier transform infrared spectrum of BN-CDs prepared in Example 1;
[0040] Figure 6 is the XPS spectrum of BN-CDs; among them, a), b), c), d) are the high-resolution XPS spectra of B 1s, C 1s, O 1s, and N1s of BN-CQD, respectively, and e) is the overall XPS spectrum.
[0041] Figure 7 The photophysical characterization spectra of BN-CDs prepared in Example 1; wherein a) is the ultraviolet absorption spectrum and luminescence spectrum of BN-CDs, b) is the photoluminescence fluorescence quantum yield of BN-CDs under different precursor molar ratio reactions, c) is the fluorescence spectrum of BN-CDs under different polar solvents, d) is the low-temperature fluorescence spectrum and low-temperature phosphorescence spectrum of BN-CDs, e) is the fluorescence decay curve of BN-CDs, and f) is the phosphorescence decay curve of BN-CDs;
[0042] Figure 8 The emission spectra of BN-CDs prepared in Example 1 in different polar solvents, wherein a) is Toluene; b) is THF, c) is DMF, d) is Ethanol, e) is Isopropanol, and f) is Methanol;
[0043] Fig. 9 The UV absorption spectrum and cyclic voltammetry curve of BN-CDs prepared in Example 1, wherein a) is the UV absorption spectrum; b) is the cyclic voltammetry curve of BN-CDs in (Bu)4NPF6 and ferrocene;
[0044] Figure 10 is a structure and performance diagram of a light-emitting diode based on boron-nitrogen co-doped carbon dots prepared by the present invention, wherein a) is a diagrammatic structure, b) is an energy level diagram, c) is the electroluminescence spectrum at different thicknesses of the electron transport layer, and d) is the external quantum efficiency-brightness curve of the CDLED device. DETAILED DESCRIPTION
[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0050] The room temperature in the present invention refers to 25±2°C.
[0051] The raw materials required for the embodiments of the present invention are all purchased from the market.
[0052] An embodiment of the present invention provides a method for preparing blue light carbon dots based on boron and nitrogen co-doping: using phenylboric acid as the first precursor and m-phenylenediamine as the second precursor, reacting at different molar ratios to prepare a series of BN-CDs (blue light carbon dots based on boron and nitrogen co-doping).
[0053] In some preferred embodiments of the present invention, phenylboric acid, m-phenylenediamine and ethanol are mixed, and the amount ratio of phenylboric acid, m-phenylenediamine and ethanol is (0.12-1.83) g: (0.11-2.16) g: (10-20) mL, followed by ultrasonic dissolution treatment at 30-60° C. for 30-60 min, and then transferred to an autoclave, and the autoclave is placed in a muffle furnace, and a high-temperature and high-pressure reaction is carried out in the muffle furnace, the reaction temperature is 180-220° C., the reaction time is 360-720 min, and then cooled to room temperature, using dichloromethane as an eluent, and separating and purifying by column chromatography to obtain a blue carbon dot solution, and obtaining BN-CDs by rotary evaporation and vacuum drying (the specific process of column chromatography separation and purification, rotary evaporation and vacuum drying is a prior art, not an invention point, and will not be repeated here.)
[0054] The embodiment of the present invention also provides a method for preparing a light-emitting diode based on blue carbon dots co-doped with boron and nitrogen: using BN-CDs as a guest material, poly (9-vinyl carbazole) as a host material, and o-dichlorobenzene as a solvent, a mixed solution of a light-emitting layer is prepared, and the mixed solution is used as a raw material of the light-emitting layer to prepare a light-emitting diode based on carbon dots. Specifically, the following steps are included:
[0055] 1) Using BN-CDs as the guest material, poly(9-vinyl carbazole) as the host material, and o-dichlorobenzene as the solvent, the amount ratio of BN-CDs, poly(9-vinyl carbazole) and o-dichlorobenzene is (0.3-2) mg: (9.7-8) mg: (1-10) mL, and preparing a light-emitting layer mixed solution;
[0056] 2) Use a soft sponge to dip into Decon-90 cleaning solution and rub the surface of the ITO (indium tin oxide film, commonly known as ITO) substrate until the water droplets on the surface are no longer attached to the wall. Use acetone, deionized water and anhydrous ethanol to ultrasonically clean for 10-30 minutes at 50-70°C, and then use a nitrogen air gun to flush out the liquid droplets on the ITO surface; then put it in an oven and dry it at 100-120°C for 2-4 hours, and finally ozone treat it for 20-60 minutes, and transfer it to a spin coating glove box filled with nitrogen for use;
[0057] 3) Spin-coating a PEDOT:PSS (alias: poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) solution onto the treated ITO substrate surface at a speed of 4000-6000 r / 30s to form a film, and annealing at 100-150°C for 15-30min to form a PEDOT:PSS film;
[0058] 4) Spin-coat the luminescent layer mixed solution prepared in step 1) onto the PEDOT:PSS film at a speed of 2000-4000r / 30s, anneal at 100-150°C for 15-30min, and prepare the electron transport layer TPBi, the electron injection layer LiF and the aluminum electrode by thermal deposition in a vacuum environment filled with nitrogen at a vacuum degree of 10- 5 Pa; the thickness of the electron transport layer is 40-80nm, the thickness of the electron injection layer is 0.5-5nm, and the thickness of the aluminum electrode is 80-150nm, thereby preparing a light-emitting diode based on boron and nitrogen co-doped blue light carbon dots.
[0059] Example 1 A method for preparing blue light-emitting carbon dots based on boron and nitrogen co-doping:
[0060] According to the molar ratio of 5:1, 0.61g of Ph-B(OH)2 (phenylboric acid) and 0.11g of m-PDA (meta-phenylenediamine) were mixed, 10mL of anhydrous ethanol was added, and the mixture was ultrasonically dissolved at 50°C for 60min. Then the mixture was transferred to an autoclave, and the autoclave was placed in a muffle furnace. A high-temperature and high-pressure reaction was carried out in the muffle furnace. The reaction temperature was 200°C and the reaction time was 360min. The mixture was then cooled to room temperature and separated and purified by column chromatography using dichloromethane as the eluent to obtain a blue carbon dot solution. Finally, a blue light carbon dot powder based on boron and nitrogen co-doping was obtained by rotary evaporation and vacuum drying, which was recorded as BN-CDs.
[0061] Figure 1 The preparation schematic diagram of BN-CDs in this embodiment 1 is shown. Phenylboronic acid and m-phenylenediamine are selected as precursors, ethanol is used as solvent, and the basic skeleton of carbon dots is constructed by solvent thermal dehydration condensation. Blue carbon dots are separated and purified by column chromatography and named BN-CDs. Phenylboronic acid is a very good carbon source because its carbon content on the benzene ring is relatively high. The benzene ring contains a boronic acid group, which can be used as a good boron source and retain the boronic acid group on the surface of CDs, thereby providing an active site. In addition, phenylboronic acid is introduced into the benzene ring to further increase the degree of conjugation and improve the rigidity of the molecule. The higher rigidity can reduce the vibration of the polycyclic aromatic ring, making it difficult for the excitation energy to be released in the form of heat due to vibration. In addition, higher structural stability is also conducive to increasing the coplanarity of the molecule, which is conducive to increasing the mobility of π electrons in the carbon core, thereby reducing the absorption energy required for the transition, reducing the probability of non-radiative transition, and facilitating the generation of fluorescence. The formed strong covalent bonds (BC, CN, etc.) and hydrogen bond networks can effectively restrict the rotation of the CDs chromophore, thereby suppressing the non-radiative recombination of triplet excitons, protecting the excited triplet excitons from quenching, promoting the phosphorescent emission of CDs, and further improving the device EQE.
[0062] Example 2 A method for preparing blue light-emitting carbon dots based on boron and nitrogen co-doping:
[0063] According to the molar ratio of 1:20, 0.12g of Ph-B(OH)2 (phenylboric acid) and 2.16g of m-PDA (meta-phenylenediamine) were mixed, 10mL of anhydrous ethanol was added, and the mixture was ultrasonically dissolved at 50°C for 60min. The mixture was then transferred to an autoclave and placed in a muffle furnace. A high-temperature and high-pressure reaction was carried out in the muffle furnace at a reaction temperature of 200°C for 360min. The mixture was then cooled to room temperature and separated and purified by column chromatography using dichloromethane as the eluent to obtain a blue carbon dot solution. Finally, a blue light carbon dot powder based on boron and nitrogen co-doping was obtained by rotary evaporation and vacuum drying, which was recorded as BN-CDs.
[0064] Example 3 A method for preparing blue light-emitting carbon dots based on boron and nitrogen co-doping:
[0065] According to the molar ratio of 15:1, 1.83g of Ph-B(OH)2 (phenylboric acid) and 0.11g of m-PDA (meta-phenylenediamine) were mixed, 10mL of anhydrous ethanol was added, and the mixture was ultrasonically dissolved at 50°C for 60min. Then the mixture was transferred to an autoclave, and the autoclave was placed in a muffle furnace. A high-temperature and high-pressure reaction was carried out in the muffle furnace. The reaction temperature was 200°C and the reaction time was 360min. The mixture was then cooled to room temperature and separated and purified by column chromatography using dichloromethane as the eluent to obtain a blue carbon dot solution. Finally, a blue light carbon dot powder based on boron and nitrogen co-doping was obtained by rotary evaporation and vacuum drying, which was recorded as BN-CDs.
[0066] Example 4
[0067] The same as Example 1, except that the high temperature and high pressure reaction is carried out in a muffle furnace, the reaction temperature is 180° C., and the reaction time is 360 min.
[0068] Example 5
[0069] The same as Example 1, except that the high temperature and high pressure reaction is carried out in a muffle furnace, the reaction temperature is 220° C., and the reaction time is 360 min.
[0070] Example 6
[0071] The same as Example 1, except that the high temperature and high pressure reaction is carried out in a muffle furnace, the reaction temperature is 200° C., and the reaction time is 540 min.
[0072] Example 7
[0073] The same as Example 1, except that the high temperature and high pressure reaction is carried out in a muffle furnace, the reaction temperature is 200° C., and the reaction time is 720 min.
[0074] Example 8
[0075] The same as Example 1, except that the ultrasonic dissolution treatment is carried out in an ultrasonic machine, the ultrasonic temperature is 30° C., and the ultrasonic time is 60 min.
[0076] Example 9
[0077] The same as Example 1, except that the ultrasonic dissolution treatment is carried out in an ultrasonic machine, the ultrasonic temperature is 60° C., and the ultrasonic time is 60 min.
[0078] Example 10
[0079] The same as Example 1, except that the ultrasonic dissolution treatment is carried out in an ultrasonic machine, the ultrasonic temperature is 50° C., and the ultrasonic time is 30 min.
[0080] Embodiment 11
[0081] The same as Example 1, except that the ultrasonic dissolution treatment is carried out in an ultrasonic machine, the ultrasonic temperature is 50° C., and the ultrasonic time is 45 min.
[0082] Comparative Example 1
[0083] Same as Example 1, except that the molar ratio of Ph-B(OH)2 to m-PDA is 1:25, and the corresponding amounts are 0.12 g of Ph-B(OH)2 (phenylboric acid) and 2.70 g of m-PDA (meta-phenylenediamine).
[0084] Comparative Example 2
[0085] Same as Example 1, except that the molar ratio of Ph-B(OH)2 to m-PDA is 20:1, and the corresponding amounts used are 2.44 g of Ph-B(OH)2 (phenylboric acid) and 0.11 g of m-PDA (meta-phenylenediamine).
[0086] Performance test
[0087] 1. Morphology test of BN-CDs
[0088] Figure 2 (a) is a transmission electron microscope (TEM) image of the BN-CDs prepared in Example 1, showing that the carbon dots are evenly dispersed with an average size of 4.22 nm.
[0089] Figure 2 b) is a high-resolution transmission electron microscope (HRTEM) image of the BN-CDs prepared in Example 1, showing the high crystallinity of the BN-CDs prepared in the present invention, with a lattice spacing of 0.21 nm, corresponding to the (100) plane spacing of graphene along the
[001] direction, further proving the almost defect-free graphene crystal structure of CDs;
[0090] Figure 2 (c) is the particle size distribution diagram of BN-CDs prepared in Example 1.
[0091] 2. Structural characteristics of BN-CDs
[0092] 1) In order to further study the intrinsic characteristics of carbon dots, the present invention studied the structure of BN-CDs prepared in Example 1.
[0093] Figure 3 The X-ray diffraction (XRD) pattern of the BN-CDs powder prepared in Example 1 is shown in FIG. Figure 3 It can be seen that there is a strong and broad peak at about 21.3°, which is due to heteroatom doping or sp 3 The deformation caused by C defects leads to amorphous carbon on the (002) crystal plane, which is a typical feature of CDs. There is a weak peak near 41.5°, corresponding to the in-plane peak (100), and the interlayer spacing is 0.21nm.
[0094] Figure 4 The Raman spectrum of BN-CDs prepared in Example 1 is shown in FIG. Figure 4 It can be seen that at 1605cm -1 The CDs have an ordered G band at 1382 cm -1 There is a disordered D band at I G / I D The ratio is 2.79, indicating that the BN-CDs prepared in the present invention have a high degree of crystallinity.
[0095] 2) In order to further study the relationship between the functional groups of carbon dots and the high fluorescence quantum yield, the present invention studied the surface functional groups of BN-CDs prepared in Example 1.
[0096] The functional groups in the BN-CDs prepared in Example 1 were analyzed by FT-IR. Figure 5 As shown. The peaks in the Fourier transform infrared spectrum were assigned, and the internal structure and functional groups on the edge of BN-CDs were further studied. The spectrum showed that the raw material phenylboronic acid had a peak at 3207 cm -1 、1442cm -1 and 1025cm -1 The characteristic absorption of can be attributed to the stretching mode of BOH, the asymmetric stretching vibration of BO and the stretching mode of CB bond. These functional groups can also be observed in BN-CDs, but the position is shifted to 3340 cm -1 、1446cm -1 and 1033cm -1, indicating that there may be interactions in BN-CDs, thus distinguishing them from the raw materials, proving the successful synthesis of BN-CDs. -1 and about 3410 cm -1 The broad peak at 1624 cm-1 is due to different vibration forms of NH, indicating the presence of amino groups. -1 The peak observed at is characteristic of aromatic groups and is attributed to C=C / C=O.
[0097] The functional groups on the surface of the precursors phenylboronic acid and m-phenylenediamine include strong electron-donating groups such as hydroxyl and amino groups. The boric acid groups on the precursors condense with the amino groups to form hydrogen bonds and BN covalent bonds, constructing the basic skeleton of carbon dots to form graphite nitrogen, making BN-CDs more rigid, reducing the vibration of the polycyclic aromatic rings in the skeleton, and making it difficult for the excitation energy to be released in the form of heat due to vibration. The strong covalent bonds (BC, CN, etc.) and hydrogen bond networks formed can effectively limit the rotation of the BN-CDs chromophore, thereby inhibiting the non-radiative recombination of triplet excitons and protecting the excited triplet excitons from quenching. Under the joint action of these groups, the carbon dots ultimately have a higher fluorescence quantum yield.
[0098] 3) In order to confirm the valence and bonding information of B, C, N, and O in the carbon dots, the present invention performs an X-ray photoelectron spectroscopy (XPS) test on the BN-CDs prepared in Example 1, see Figure 6 In a)-e), the XPS full spectrum e) shows the presence of signal peaks of B 1s (191.1 eV), C 1s (284.1 eV), N 1s (400.0 eV) and O 1s (532.6 eV), among which the content of B element is as high as 10.38%. XPS confirms the FTIR data, indicating that BN-CDs are composed of only B, C, N and O. This shows that there are no metal or other non-metallic impurities in the elemental composition of BN-CDs. Compared with traditional OLED materials or QLED materials, the preparation of CDs is widely available, metal-free, low-cost and green.
[0099] The high-resolution B 1s, C 1s, N 1s and O 1s spectra of BN-CDs are shown in Figure 2. Figure 6a)-e). The high-resolution XPS spectrum of B 1s shows three peaks at 191.1, 190.6 and 189.9 eV, which can be assigned to BO, BN and BC. The high-resolution XPS spectrum of C 1s shows four different forms of peaks: C=O (285.9 eV), CN (284.9 eV), C= C / CC (284.0 eV) and CB (283.5 eV). The high-resolution XPS spectrum of N 1s has three peaks at 398.8, 399.9 and 400.7 eV, corresponding to NB, NC and NH, respectively. The high-resolution XPS spectrum of O1s spectrum shows the presence of O=C bonds (531.2 eV), OB bonds (532.3 eV) and OC bonds (533.5 eV) in CDs.
[0100] 3. Optical properties of BN-CDs
[0101] 1) Figure 7 Figure a) is the UV-visible absorption spectrum and fluorescence spectrum of the BN-CDs prepared in Example 1. It can be seen from the UV-visible absorption spectrum of BN-CDs that the UV absorption peak at around 300 nm is the π-π* electron transition of the aromatic ring, and a strong absorption band is exhibited at around 350-450 nm, corresponding to the characteristic absorption peak generated by the n-π* transition in BN-CDs.
[0102] from Figure 7 From the fluorescence spectrum of a), we can see that the fluorescence spectrum of BN-CDs presents a single peak emission with an emission peak at 430 nm. And it can be found that the peak has a downward swing, resulting in a wide half-peak width of about 60 nm. This is because the fluorescence peak intensity at 430 nm is too high, and there is a weak luminescence peak at a long wavelength near the peak. In the presence of oxygen at room temperature, its luminescence intensity is quenched, resulting in weak luminescence.
[0103] Figure 7 b) is the photoluminescence quantum yield of BN-CDs prepared in Example 1. It can be seen from the figure that at the optimal precursor ratio of 5:1, the photoluminescence quantum yield (PLQY) of BN-CDs is 86.41%.
[0104] Figure 7Figure c) is the solvation effect spectrum of BN-CDs prepared in Example 1. The normalized photoluminescence curves of BN-CDs in aprotic solvents of different polarities, including n-hexane, toluene, dichloromethane (DCM), tetrahydrofuran (THF), and acetonitrile (ACN), show that the center of the photoluminescence emission position of BN-CDs changes slightly with the change of the polarity of the aprotic solvent, which reflects that the environmental sensitivity of CDs is low, that is, the passivation structure on the surface of BN-CDs plays a good protective role, which is conducive to application in LED devices.
[0105] Figure 7 Figure d) shows the low-temperature fluorescence spectrum and low-temperature phosphorescence spectrum of BN-CDs prepared in Example 1. From the low-temperature fluorescence spectrum curve, it can be seen that in addition to the maximum emission peak at 430 nm, there is also a shoulder peak at 485 nm, which is consistent with the swing phenomenon of the fluorescence spectrum curve measured at room temperature, which shows that the emission peak at 485 nm comes from phosphorescence emission. In the low-temperature phosphorescence spectrum, the maximum emission peak can be observed at 510 nm, which further confirms the existence of room temperature phosphorescence. Therefore, the photoluminescence mechanism of CDs may come from multiple complex centers in the carbon core.
[0106] Figure 7 Figure e) is the fluorescence decay lifetime curve of BN-CDs prepared in Example 1. It can be seen from the figure that the decay lifetime presents a single exponential decay. The results are shown in Table 1.
[0107] Figure 7 Figure f) is the phosphorescence decay lifetime curve of the BN-CDs prepared in Example 1. It can be seen from the figure that the decay lifetime presents a multi-exponential decay. The results are shown in Table 1. The existence of multiple lifetimes also indicates that the emission of BN-CDs comes from multiple complex centers in the carbon core.
[0108] Table 1
[0109]
[0110] The present invention also explores the effect of solvents on the optical properties of BN-CDs and the photoluminescence mechanism of BN-CDs. Using protic solvents of different polarities such as methanol, ethanol, isopropanol and aprotic solvents such as toluene, tetrahydrofuran (THF) and N, N-dimethylformamide (DMF) as solvents, different excitation wavelengths are used to excite BN-CDs in solvents of different polarities, such as Figure 8As shown in a)-f). Under different excitation wavelengths, the center of the photoluminescence emission position of BN-CDs is basically unaffected, which proves the excitation wavelength independence of BN-CDs. In addition, compared with the aprotic solvents toluene, tetrahydrofuran and N,N-dimethylformamide, the fluorescence peak of BN-CDs is dominated by 430 nm, while in the protic solvents methanol, ethanol and isopropanol, it can be clearly found that the phosphorescence peak around 500 nm is dominant. This may be due to the fact that the formed hydrogen bond network can effectively restrict the rotation of the BN-CDs chromophore, thereby inhibiting the non-radiative recombination of triplet excitons and protecting the excited triplet excitons from quenching, thereby enhancing the phosphorescence emission.
[0111] In summary, BN-CDs first possess the typical characteristics of carbon core emission: (i) single exponential decay; (ii) independence from excitation wavelength. These all prove that the photoluminescence behavior is emitted inside the carbon core, proving that its photoluminescence mechanism is carbon core state emission. Secondly, solvation experiments and multi-exponential decay of phosphorescence lifetime also prove the existence of phosphorescence emission. Therefore, using BN-CDs with dual fluorescence and phosphorescence emission to prepare electroluminescent diodes is expected to utilize triplet excitons to improve device efficiency.
[0112] The present invention estimates the HOMO and LUMO energy levels of BN-CDs by cyclic voltammetry, such as Fig. 9 The present invention uses a glassy carbon electrode as a working electrode, a platinum sheet as a counter electrode (auxiliary electrode), and an Ag / Ag + The cyclic voltammetry (CV) curve was drawn using a standard three-electrode system composed of a reference electrode. The CV curve was scanned in acetonitrile containing 0.1 M tetrabutylammonium, ammonium hexafluorophosphate ((Bu)4NPF6) was used as the electrolyte, and ferrocene was used to calibrate the potential according to the following formula:
[0113] E HOMO =-[E ox +E(Fc / Fc + ) + 4.8]
[0114] E g =1240 / λ onset
[0115] E LUMO =E HOMO + E g
[0116] Among them, E HOMO is the highest molecular occupied orbital; E ox is the sample initial energy level; Fc / Fc + is the starting energy level of ferrocene;
[0117] λ onsetis the starting absorption wavelength of UV-visible absorption; E g is the energy gap; E LUMO is the lowest molecular occupied orbital.
[0118] According to the results of cyclic voltammetry, the E g The energy level of BN-CDs is close to that of the main material poly(9-vinylcarbazole) (PVK).
[0119] Example 12
[0120] 1) Weigh 0.3 mg of the BN-CDs prepared in Example 1 and 9.7 mg of poly(9-vinylcarbazole) (PVK), use 2 mL of o-dichlorobenzene as solvent, and prepare a 3% device light-emitting layer mixed solution;
[0121] 2) Use a soft sponge dipped in Decon-90 cleaning solution to rub the surface of the ITO (indium tin oxide film, commonly known as ITO) substrate until the water droplets on the surface are no longer attached to the wall. Use acetone, deionized water and anhydrous ethanol to ultrasonically clean for 20 minutes at 70°C, and then use a nitrogen air gun to flush away the liquid droplets on the ITO surface; then put it in an oven and dry it at 120°C for 2 hours, and finally ozone treat it for 30 minutes, and transfer it to a spin coating glove box filled with nitrogen for use;
[0122] 3) Spin-coating a PEDOT:PSS (alias: poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) solution onto the treated ITO substrate surface at a speed of 5000r / 30s to form a film, and annealing at 150°C for 20min on a heating table to form a PEDOT:PSS film;
[0123] 4) Spin-coating the luminescent layer mixed solution prepared in step 3) onto the PEDOT:PSS film at a speed of 2500 r / 50 s, annealing at 150° C. for 20 min on a constant temperature heating table, and transferring to a vacuum evaporation chamber filled with nitrogen for use;
[0124] 5) In vacuum environment 10 -5 Pa, the electron transport layer TPBi 80nm (thickness, the same below), the electron injection layer LiF 1nm and the aluminum electrode 100nm were prepared by thermal deposition method to prepare a light-emitting diode based on boron and nitrogen co-doped carbon dots, namely CDLED.
[0125] Example 13
[0126] Same as Example 12, except that in step 5), the electron transport layer TPBi is 40 nm.
[0127] Embodiment 14
[0128] Same as Example 12, except that in step 5), the electron transport layer TPBi is 60 nm.
[0129] Embodiment 15
[0130] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 2.
[0131] Example 16
[0132] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 3.
[0133] Embodiment 17
[0134] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 4.
[0135] Embodiment 18
[0136] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 5.
[0137] Embodiment 19
[0138] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 6.
[0139] Embodiment 20
[0140] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 7.
[0141] Embodiment 21
[0142] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 8.
[0143] Embodiment 22
[0144] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 9.
[0145] Embodiment 23
[0146] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 10.
[0147] Embodiment 24
[0148] Same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Example 11.
[0149] Comparative Example 3
[0150] The same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Comparative Example 1.
[0151] Comparative Example 4
[0152] The same as Example 12, except that in step 1), the BN-CDs prepared in Example 1 are replaced by the BN-CDs prepared in Comparative Example 2.
[0153] CDLED device performance test of BN-CDs
[0154] The high fluorescence quantum yield and excellent phosphorescence properties of BN-CDs are conducive to the development of its application in LEDs, promoting the development of a new generation of display technology. The device structure adopts a simple and reasonable design, with PEDOT:PSS as the hole injection layer, TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)]) as the hole transport layer, and the light-emitting layer adopts a host-guest doping system. The light-emitting layer uses BN-CDs as the guest material, poly(9-vinylcarbazole) (PVK) as the host material, 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) as the electron transport layer, and LiF / Al as the double-layer cathode.
[0155] In the present invention, BN-CDs is used as the guest material of the light-emitting layer, and the thickness of the electron transport layer TPBi is adjusted to be 80 nm (Example 12, i.e., TPBi 80 ), the thickness of TPBi is 40 nm (Example 13, i.e., TPBi 40 ) and the thickness of TPBi is 60nm (Example 14, i.e., TPBi 60 ) Detailed data of the three devices are shown in Table 2.
[0156] Table 2
[0157] Electron transport layer ETL [nm] <![CDATA[Starting voltage V on [V]]]> <![CDATA[Electroluminescence position λ EL [nm]]]> Half peak width FWHM [nm] <![CDATA[Maximum luminance L (max) [cd m -2 > Maximum external quantum efficiency EQE[%] 40 4.7 440 52 686.20 0.78 60 4.0 440 51 577.80 2.66 80 4.0 440 51 1305.00 6.98
[0158] Fig.10 a) is a diagrammatic structure of a light-emitting diode based on boron-nitrogen co-doped carbon dots prepared by the present invention; b) is an energy level diagram of a light-emitting diode based on boron-nitrogen co-doped carbon dots prepared; c) is an electroluminescence spectrum of the electron transport layer TPBi at different thicknesses; d) is an external quantum efficiency-brightness curve of a light-emitting diode based on boron-nitrogen co-doped carbon dots prepared in Examples 12-14. Fig.10 As shown in c) and d), the light emission position of the CDLED under different thicknesses of the electron transport layer TPBi is around 440 nm, with no obvious effect. As the thickness increases, the device efficiency EQE value of the CDLED increases from 0.78% to 2.66 and 6.98%. Among them, the CDLED device with a TPBi thickness of 80 nm has the highest efficiency. This is because the thicker electron transport layer also acts as a hole blocking layer, effectively blocking the transmission of holes, better regulating the injection and distribution of electrons and holes, and improving the matching degree of electron and hole injection, effectively increasing the probability of electron and hole recombination, thereby improving the luminous efficiency of the device. This is also the first electroluminescent device prepared based on boron and nitrogen co-doped fluorescent and phosphorescent dual-emitting carbon dots.
[0159] The results show that by regulating the thickness of the electron transport layer TPBi so that the carrier injection and transport in the device are in a balanced state, the device efficiency can be improved; the presence of phosphorescence also enables the effective utilization of triplet excitons, thereby increasing the antisystem crossing rate, and ultimately allowing the device's external quantum efficiency to break through the 5% limit of traditional fluorescent devices.
[0160] The performance test results of the CDLED devices prepared in Examples 15-24 are shown in Table 3.
[0161] Table 3
[0162] Electron transport layer ETL [nm] <![CDATA[Starting voltage V on [V]]]> <![CDATA[Electroluminescence position λ EL [nm]]]> Half peak width FWHM [nm] <![CDATA[Maximum luminance L (max) [cd m -2 > Maximum external quantum efficiency EQE[%] Embodiment 15 4.7 441 55 676.2 1.10 Example 16 4.7 442 55 872.0 1.14 Embodiment 17 5.5 440 55 611.3 0.86 Embodiment 18 4.7 440 55 654.6 1.41 Embodiment 19 4.5 440 55 873.4 0.77 Embodiment 20 4.5 440 55 826.9 0.78 Embodiment 21 4.5 440 54 904.5 1.19 Embodiment 22 4.7 440 54 690.9 1.26 Embodiment 23 5.5 440 55 591.7 1.26 Embodiment 24 5.5 440 55 530.1 1.39
[0163] The performance test results of the CDLED devices prepared in Comparative Example 3-4 are shown in Table 4.
[0164] Table 4
[0165] Electron transport layer ETL [nm] <![CDATA[Starting voltage V on [V]]]> <![CDATA[Electroluminescence position λ EL [nm]]]> Half peak width FWHM [nm] <![CDATA[Maximum luminance L (max) [cd m -2 > Maximum external quantum efficiency EQE[%] Comparative Example 3 5.5 440 56 665.8 0.20 Comparative Example 4 5.5 440 56 272.5 0.08
[0166] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing blue light-emitting carbon dots based on boron and nitrogen co-doping, characterized in that: The following steps are involved: Phenylboric acid, m-phenylenediamine and anhydrous ethanol are mixed, subjected to solvothermal reaction after ultrasonication, the reactants are cooled to room temperature, separated and purified by column chromatography, and then subjected to rotary evaporation and vacuum drying to obtain blue light-emitting carbon dots based on boron-nitrogen co-doping; The dosage ratio of the phenylboric acid, m-phenylenediamine and anhydrous ethanol is (0.12-1.83) g: (0.11-2.16) g: (10-20) mL; The temperature of the ultrasound is 30-60°C and the time is 30-60min; The temperature of the solvent thermal reaction is 180-220° C. and the time is 360-720 min.
2. A blue light carbon dot based on boron and nitrogen co-doping, characterized in that: It is prepared by the preparation method described in claim 1.
3. Use of the blue carbon dots based on boron and nitrogen co-doping according to claim 2 in the preparation of light-emitting diodes.
4. A method for preparing a light emitting diode, characterized in that: The invention comprises the following steps: using the blue light-emitting carbon dots based on co-doping of boron and nitrogen as claimed in claim 2 as the guest material, poly (9-vinyl carbazole) as the main material, and o-dichlorobenzene as the solvent to prepare a mixed solution of the light-emitting layer; cleaning the surface of the ITO substrate, drying it, and then treating it with ozone, and placing it in a nitrogen environment for standby use; spin-coating the PEDOT:PSS solution onto the treated surface of the ITO substrate to form a film, and annealing it at 100-150°C for 15-30min to form a PEDOT:PSS film; spin-coating the mixed solution of the light-emitting layer onto the PEDOT:PSS film, and then annealing it at 100-150°C for 15-30min, and preparing an electron transport layer, an electron injection layer and an aluminum electrode by a thermal deposition method in a vacuum environment filled with nitrogen, so as to prepare a light-emitting diode based on blue light-emitting carbon dots co-doped with boron and nitrogen.
5. The preparation method according to claim 4, characterized in that: The dosage ratio of the blue light carbon dots based on boron and nitrogen co-doping, poly(9-vinylcarbazole) and o-dichlorobenzene is (0.3-2) mg: (9.7-8) mg: (1-10) mL.
6. The preparation method according to claim 4, characterized in that: The thickness of the electron transport layer is 40-80 nm, the thickness of the electron injection layer is 0.5-5 nm, and the thickness of the aluminum electrode is 80-150 nm.
